The Study of Translation Ideology and Its Accuracy in Qur'anic Vocabulary for Women - Syihabuddin, Syihabuddin; Aryanti, Tutin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
Gender issues have garnered considerable attention from researchers, women's campaigners, and society at large. The perspectives held by individuals are grounded on cultural, religious, and ideological frameworks. The religious perspectives, such as those rooted in Islam, draw upon the Qur’an and its translation as primary source. The comprehension of translation is purportedly intricately linked to the underlying ideology that informs the translation process. This study aimed to offer a formulation of ideology that may be utilized to sustain the notion of gender as shown in the translated text. In order to accomplish this objective, an analysis was conducted on the translation of Quranic verses that encompass words pertaining to women, specifically al-umm, al-wālidah, az-zauj, al-'imra`ah, an-nisa`, an-niswah, and al-untsa, employing a series of steps. Those steps were examining the translation technique, identifying the underlying ideology associated with the technique, evaluating the accuracy of the conveyed meaning, engaging in a discussion, and formulating a conclusion. Moreover, this study included the cumulative sum of the seven terms amounted to 146 units, which were extracted from The Qur’an and Its Translation as published by the Ministry of Religion. The findings of this study indicate that gender concepts are translated in a literal manner. This approach demonstrates the adoption of the foreignization ideology in translation, which prioritizes the source language and the precise conveyance of its meaning. The utilization of the idea is further reinforced by the assertion that the seven terms are faithfully translated, except for the term imra'ah, which is rendered as wife, a translation that is deemed to be inaccurate.